ICHTHYOFAUNAL DIVERSITY AND CAPTURE FISHERIES IN OVIA RIVER, EDO STATE, NIGERIA. - OLOWO, Ukpamufo Cyril; EGUN, Nkonyeasua Kingsley; OMORUWOU, Precious E; OBOH, Ijeoma Patience (Indonesian Fisheries Research Journal, 2023)
The increasing reduction in the quantity and diversity of fish catch from freshwater bodies, has become a global concern due to its impacts on human nutrition, economy, culture and zoological spectrum of the aquatic ecosystem. This study ascertained the ichthyofauna composition and diversity of Ovia River, Edo State and its capacity to sustain capture fisheries.  Fish catch from April, 2021 to March 2022 showed that Ovia River is congenial for 26 fish species of commercial importance, belonging to 5 orders, 13 families, 19 genera and 26 species. This is indicative of a rich diversity with Mormyridae dominant with 7 species, Cichlidae with 6 species, Mochokidae and Characidae with 2 species each, Ariidae, Bagridae, Channidae, Cyprinidae, Hepsetidae, Malapterunidae, Notopteridae, Pantodontidae and Schilbeidae with 1 species each. Fish species abundance showed that Cichlidae was the highest 61 individuals (39.61%), while Ariidae and Hepsetidae with 1 individual each (0.65%) were the least. The dominance and abundance of the highly priced Mormyridae and Cichlidae species implies that the water body has the capacity to sustain artisanal fisheries activities. This study has provided useful data for fisheries management and ecological studies of inland freshwater resources in Nigeria.